Understanding the preferences of rural communities for adaptation to 21st-century sea-level rise: A case study from the Samoan islands - Richard Nathan Crichton; Miguel Esteban; Motoharu Onuki (Climate Risk Management, 2020)
This paper explores the perceived adaptation preference of rural island communities in addressing future climate change risks, particularly those concerning sea-level rise. The research explores the role of culture and local politics, and differences among various age and gender groups within the community regarding preferred adaptation pathways for coping with the impacts of future sea-level rise. A participatory action approach, in the form of a community workshop, was employed, which separated participants into community identified groupings. Differences in community groups' adaptation preferences emerged, though the range of adaptation measures considered were limited, probably due to the participants’ limited exposure to adaptation mechanisms in their immediate surroundings. Overall, the communities surveyed tended to be conservative, especially in their attitudes towards western adaptation solutions developed in non-island contexts.